Kéntros, another Term of Mesopotamian Origin in the Ethiopian Astronomy - Lourié, Basil (Aethiopica, 2012)
The Ethiopic term kentros “1/30” goes back to Akkadian mišlu through a lost meaning of the Greek astronomical term κέντρον.